2020
DOI: 10.1016/j.bbrc.2020.04.007
|View full text |Cite
|
Sign up to set email alerts
|

A possible strategy to fight COVID-19: Interfering with spike glycoprotein trimerization

Abstract: The recent release of COVID-19 spike glycoprotein allows detailed analysis of the structural features that are required for stabilizing the infective form of its quaternary assembly. Trying to disassemble the trimeric structure of COVID-19 spike glycoprotein, we analyzed single protomer surfaces searching for concave moieties that are located at the three protomer-protomer interfaces. The presence of some druggable pockets at these interfaces suggested that some of the available drugs in Drug Bank could destab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 14 publications
0
25
0
6
Order By: Relevance
“…The trimer-binding interface between individual S protomers and the interaction sites of trimerization are not fully characterized for the SARS-CoV-2. Recent studies have suggested several residues that contribute to the formation or to stabilize the S trimeric structure; and most of them are located at the S2 subunit (mainly in the S2-NTD, FP, CR, HR1, CH and CD) [53] , [54] , [55] , [56] , [57] , [58] . Thirteen of these residues (E702, Y707, N709, N710, Y789, K790, K795, F797, G798, T859, G891, Q895, F898) are described by multiple authors and represent CDR or T-RHS for drug targeting highlighted in our study [53] , [54] , [55] , [56] , [57] , [58] .…”
Section: Resultsmentioning
confidence: 99%
“…The trimer-binding interface between individual S protomers and the interaction sites of trimerization are not fully characterized for the SARS-CoV-2. Recent studies have suggested several residues that contribute to the formation or to stabilize the S trimeric structure; and most of them are located at the S2 subunit (mainly in the S2-NTD, FP, CR, HR1, CH and CD) [53] , [54] , [55] , [56] , [57] , [58] . Thirteen of these residues (E702, Y707, N709, N710, Y789, K790, K795, F797, G798, T859, G891, Q895, F898) are described by multiple authors and represent CDR or T-RHS for drug targeting highlighted in our study [53] , [54] , [55] , [56] , [57] , [58] .…”
Section: Resultsmentioning
confidence: 99%
“…Another approach could be to target viral assembly. The formation of the S spike trimer might not be a fast and direct process, so there is a chance to block the quaternary structure of the spike ( Bongini et al, 2020 ). Analysis of protein-protein interfaces of the spike has led to the prediction of ligands (Ergoloid, Darifenacin, 5-methyl-tetrahydrofolic acid, Buclizine, Saquinavir, Solifenacin, Sorafenib, tetrahydrofolic acid) that potentially could affect this process ( Bongini et al, 2020 ).…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…S glycoprotein is highly immunogenic, and it is a promising target for drug design 11 . We showed that a combination of four 20-mer synthetic peptides disrupting SARS-CoV S heterotrimer reduced or completely inhibited infectivity in vitro 12 .…”
Section: Introductionmentioning
confidence: 99%